Studies on the effect of cocoa pod as filler in polyester composites (2008)
This work investigates the effects of surface treatment on cocoa pod on the mechanical properties of polyester composites. Reinforcement varying between 0% w/w to 10% was used in the preparation of the polyester composite specimens. Tensile and hardness tests were carried out on the test specimens with and without reinforcements and the effect of loading on the mechanical properties were correlated. This work has a significant impact for the conversion of waste products, especially cocoa pod that pollutes the environment to engineering materials. The study found that apart from the common use of cocoa pod in the soap making industry, it would also become important in engineering materials fabrication. This has implication for the wealth creation programme embedded in the vision 20, 2020 target on the floor.